Virtual Music Experiences in the Metaverse: Digital Twin - Beghin, Tom (Ghent Wintercircus, 2024)
Final schowcase event (“Digital Twin”) of Virtual Music Experiences in the Metaverse, a multi-year research project with PXL Music (Hasselt) and Digital Arts and Entertainment (Kortrijk), funded by VLAIO
Abstract:This interdisciplinary research project, with sound recording engineers at PXL Music (Hasselt) and video animation researchers at Howest (Kortrijk), has explored the making of digital twins. Tom Beghin recorded a short piece by W. A. Mozart (the third movement of the Sonata in E-flat Major, K 282), using a replica of a Stein fortepiano (by Chris Maene, 2016, after an original of 1788). Digital twins were produced both of instrument and performer (using 3D scanning and MetaHuman Creator). Beghin then played the recorded piece again, using the same instrument and wearing an X Sense Suit, while his movements were mapped using techniques like Mocap and Optitrack (for finger tracking, body movement, and face animations). Meanwhile, virtual acoustic renderings of two performance venues were combined with animated visual reconstructions of De Kreun (a modern concert hall in Kortrijk) and the ceremonial room of D’Hane-Steenhuyse (an 18th-century palace in Ghent). The result is an interactive video presentation where all aspects of the animation are combined and synchronized, and where the user, wearing binaural headphones and a VR glasses, can freely walk through a chosen virtual space, randomly switching between D’Hane-Steenhuyse and De Kreun, while fluidly experiencing a “digital twin” performance.
FRIS
1
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850